Mobile air-decontamination units: Can they be used for immunocompromised patients at high risk for fungal infections? - Joris Voisin; Jacqueline Shum Cheong Sing; Claire Terreaux-Masson; Carola Pierobon; Anne Thiebaut-Bertrand; Hervé Pelloux; Caroline Landelle; Marie-Pierre B (Elsevier, 2024)
Immunocompromised patients in the hematology department are usually hospitalized in areas protected by the high-efficiency particulate air (HEPA) filtration system. Renovations may require moving these patients at risk for invasive fungal infection to areas without HEPA. Mobile air handling units may be a solution in these cases. For renovation purposes, we evaluated the efficiency of mobile air handling units called Plasmair® as well as their optimization, by comparing two generations of devices.Particle counts were performed to determine a particle cleanliness classification according to the ISO 14644-1 standard (high ISO classes correspond to a degraded particulate cleanliness). Mycological air samples were also taken to determine the percentage of positive samples and the median number of filamentous fungi colonies.Without air treatment, only 18 % (38/216) of particle counts were classified as ISO 6. With the use of mobile air treatment units, this proportion increased to 71 % (205/288). The positivity rate of mycological samples without air treatment was 86 % (31/36) with a median number of fungal colonies of 3 (1-5)/0.5m3. A significant decrease in fungal pressure was observed when using Plasmair®. Percentages of positive air samples and the median number of colonies found between the old generation Plasmair® (T2006) and the new generation Plasmair® (Guardian) were significantly different, respectively 55.6 % (20/36) versus 22.2 % (8/36) and 1(0-1) versus 0 (0-0).Finally, we confirm Plasmair® were effective in reducing airborne fungal pressure, the new generation especially. However, they were not effective enough to obtain negative mycological air samples as usually observed with the HEPA system, whatever the generation.